2012
DOI: 10.1128/jcm.00994-11
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Reproducibility of the Broth Microdilution Method for Susceptibility Testing of Nocardia Species

Abstract: Antimicrobial susceptibility testing (AST) of clinical isolates of Nocardia is recommended to detect resistance to commonly used antimicrobial agents; such testing is complicated by difficulties in inoculum preparation and test interpretation. In this study, six laboratories performed repetitive broth microdilution testing on single strains of Nocardia brasiliensis, Nocardia cyriacigeorgica, Nocardia farcinica, Nocardia nova, and Nocardia wallacei. For each isolate, a total of 30 microdilution panels from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 15 publications
3
46
0
8
Order By: Relevance
“…While in-house prepared panels are specified in that document, we have demonstrated the suitability of the Sensititre Rapmyco microdilution panel for the determination of antimicrobial susceptibility patterns of clinical isolates of Nocardia spp. MIC values for the three control strains, N. nova ATCC BAA-2227, N. asteroides ATCC 19247 T , and N. farcinica ATCC 23826, were highly reproducible and correlated well with expected resistance profiles (7,20,21). The MIC values are published here to assist other clinical laboratories in implementing quality control guidelines for the validation of Nocardia antimicrobial susceptibility testing assays using this commercial panel.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…While in-house prepared panels are specified in that document, we have demonstrated the suitability of the Sensititre Rapmyco microdilution panel for the determination of antimicrobial susceptibility patterns of clinical isolates of Nocardia spp. MIC values for the three control strains, N. nova ATCC BAA-2227, N. asteroides ATCC 19247 T , and N. farcinica ATCC 23826, were highly reproducible and correlated well with expected resistance profiles (7,20,21). The MIC values are published here to assist other clinical laboratories in implementing quality control guidelines for the validation of Nocardia antimicrobial susceptibility testing assays using this commercial panel.…”
Section: Discussionmentioning
confidence: 73%
“…Prior to this study, non-Nocardia, rapidly growing bacteria were recommended as QC strains for susceptibility testing, despite their very different growth characteristics during susceptibility testing. As an outcome of the work of Conville et al (7), N. nova ATCC BAA-2227 was recommended as the Nocardia reference strain for antimicrobial susceptibility testing of Nocardia spp. Our testing of N. nova ATCC BAA-2227 showed that not only were our results reproducible over 20 repeat tests but we also obtained MICs that were within the mode Ϯ 1 dilution for all antimicrobials tested in the Conville et al study (7), except for two drugs (amikacin and imipenem) where the Sensititre Rapmyco panel did not include dilutions as low as those on the in-house study panel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent CLSI multicenter study among six laboratories using the same strains of Nocardia and the same lot numbers of susceptibility panels, media, etc., multiple laboratories reported discrepancies in MIC interpretations for sulfonamides (5). This multicenter study showed that careful training and close scrutiny of the 80% inhibition endpoint were necessary to produce accurate MIC results.…”
Section: Discussionmentioning
confidence: 99%
“…The current study and the CLSI multicenter study emphasized the necessity for laboratory proficiency testing with unusual organisms, such as Nocardia (5). Unfortunately, there is no standardized proficiency testing program currently available, including from the College of American Pathologists (CAP).…”
Section: Discussionmentioning
confidence: 99%